Data acquisition system for a neutron spectrometer with a remote diamond detector. (1st July 2022) - Khilchenko, A.; Kvashnin, A.; Zubarev, P.; Ivanenko, S.; Puryga, E.; Moiseev, D.; Lizunov, A.
Abstract: The article presents the design and first test results of the neutron spectrometer with count rate up to 7 × 10 6 events per second with remote detector based on artificial diamond, intended for use on burning plasma experiments. The spectrometer consists of the broadband low-noise amplifier and the data acquisition and processing unit. The design of the amplifier with characteristic impedance matching of the cable line by the dynamic resistance of the transistor base-emitter junction is considered. The data acquisition and processing unit is realized using a real-time event-processing algorithm based on harmonic data analysis. This algorithm includes effective techniques for detecting and excluding overlaps and suppression of fluctuations in the baseline level corresponding to zero signal.